2016
DOI: 10.1080/00071668.2016.1200013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracted galactoglucomannan oligosaccharides from pine wood (Pinus brutia) onSalmonella typhimuriumcolonisation, growth performance and intestinal morphology in broiler chicks

Abstract: An in vitro and in vivo study was conducted to evaluate the fermentability of isolated galactoglucomannan oligosaccharides (GGMs) and the influence of their feeding on shedding and colonisation of Salmonella typhimurium, growth performance and intestinal morphology in broiler chicks. The in vitro data demonstrated that three probiotic lactic acid bacteria namely Lactobacillus casei, L. plantarum and Enterococcus faecium were able to ferment the extracted oligosaccharides and other tested sugars on a basal de M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…Therefore, increased duodenal villus height and the ratio of the villus height to crypt depth in the broilers fed ELBG diet could improve their nutrients digestibilities in this study. Similar result was observed in broiler chicks fed diet with GMOS by Rajani et al (2016). Brufau et al (2015) found in a study of infected Salmonella chickens that the 0.1% galactomannan-rich diet group had longer fluff lengths than the negative control group (Salmonella infection) and the antibiotic group, indicating half Lactomannan has the ability to increase the surface area of the epithelium.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, increased duodenal villus height and the ratio of the villus height to crypt depth in the broilers fed ELBG diet could improve their nutrients digestibilities in this study. Similar result was observed in broiler chicks fed diet with GMOS by Rajani et al (2016). Brufau et al (2015) found in a study of infected Salmonella chickens that the 0.1% galactomannan-rich diet group had longer fluff lengths than the negative control group (Salmonella infection) and the antibiotic group, indicating half Lactomannan has the ability to increase the surface area of the epithelium.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, we were able to observe a significant increase in the duodenum villi height of the treated group in most samplings, as previously described in healthy broilers [ 15 ]. A similar increase in villus height in the jejunum of broilers given supplements of probiotics or prebiotics and challenged with S. Typhimurium has been reported [ 2 , 6 , 32 , 40 , 42 , 44 , 45 ]. Fermented soybean, butyric acid, sodium butyrate, oligosaccharides, zinc, and dietary clay supplementation in S. Typhimurium-challenged broilers resulted in an increase in villi height in the small intestine, mitigating Salmonella spp.…”
Section: Discussionsupporting
confidence: 70%
“…Many authors have reported shortening of villi after a Salmonella spp. challenge [ 2 , 6 , 7 , 29 , 35 , 39 , 40 , 41 , 42 , 43 ], which implies difficulty in absorption capacity and a reduction in body weight gain [ 29 , 40 , 41 , 44 ]. In our study, we were able to observe a significant increase in the duodenum villi height of the treated group in most samplings, as previously described in healthy broilers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chicken intestine is continuously exposed to pathogenic bacteria via contaminated feed and water. Salmonella Typhimurium (ST), a major serotype of Salmonella, can infect broiler chickens, leading to decrease in their growth and food-borne diseases in humans (Rajani, et al, 2016). ST infects intestinal cells and macrophages in the small and large intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%